POLEMIK KEWENANGAN MAHKAMAH KONSTITUSI MENGUJI PERATURAN YANG MENGATUR EKSISTENSINYA - Brandon David; Diva Anastasya Suharto; Leslie Kwek (Fakultas Hukum Universitas Tarumanagara, 2020)
Constitutional Court’s authority as a state institution that was created through the fourth amendment of the 1945 Constitution is mandated in paragraph 24C of 1945. Contitution essencially, Constutional Court’s has been given a role as a patron of constitution. Since Constitutional Court’s is the only one that has authority to review law to the state institution.Constituional Court’s has various functions, including performing constitutional review, where it ensures that legislation complies with the Constitution, including the human rights provisions, and can invalidate legislative provisions that it finds to be unconstitutional.Under this authority, everyone is allowed to bring unconstitutional statutes before the Constitutional Court’s. Accordingly the Controversy regarding the constitutional Court’s authority arises to do a review of Constution in Constitutional Court’s. The Controversy is based on contradiction between to formal legal principles, which the two are binding. This article then concludes with an analysis of the controversy on constitutional Court’s authority issues that remain.